2016
DOI: 10.5942/jawwa.2016.108.0102
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Edge Shape on Characteristics of Flow Under Vertical Gates

Abstract: Gates are useful structures that are widely used in open channels for controlling discharge and water level. In this article, to study the flow passing under a gate, five gates with different‐shaped edges are numerically simulated. The contraction coefficient, discharge coefficient, pressure distribution behind the gate, and the pressure distribution on the channel bottom near the gate were investigated with models in free flow conditions. The analyses were performed for six water depths. The results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…They indicated that nappe breakers placed on the trapezoidal labyrinth weirs and circular labyrinth weirs reduced the discharge coefficient by up to 4% compared to an un-amended weir. Numerical methods have been used by various researchers in recent decades [12][13][14][15][16][17]. Shaghaghian and Sharifi [18] investigated the characteristics of flow in triangular labyrinth weirs using FLUENT.…”
Section: Figure 1 -Labyrinth Weir In a Channel With Converging Wallsmentioning
confidence: 99%
“…They indicated that nappe breakers placed on the trapezoidal labyrinth weirs and circular labyrinth weirs reduced the discharge coefficient by up to 4% compared to an un-amended weir. Numerical methods have been used by various researchers in recent decades [12][13][14][15][16][17]. Shaghaghian and Sharifi [18] investigated the characteristics of flow in triangular labyrinth weirs using FLUENT.…”
Section: Figure 1 -Labyrinth Weir In a Channel With Converging Wallsmentioning
confidence: 99%
“…The outflow B.C. is applied to prevent the effects of the outside conditions of the solution network [28]. Also, the Wall boundary condition was defined for walls and channel bed which act as virtual frictionless walls [29].…”
Section: Specifications Of the Airfoil-shaped Pier Model And Computatmentioning
confidence: 99%
“…If F = 0, the cell is completely full of air, and if F = 1, the cell is full of water. The free surface occurs where F = 0.5 (Daneshfaraz et al 2016a).…”
Section: Continuity Equations Momentum and Free Surfacementioning
confidence: 99%